Strategi Bangku Pelosok dalam Pemberdayaan Pendidikan di Kabupaten Gowa - Idris, Musfira; Muhammad Said, Nurhidayat; Haeruddin, (Jurnal Berita Sosial, 2025)
This study aims to explore the strategies implemented by the Bangku Pelosok organization in improving access to and quality of education for communities in Ballassuka Village, Tombolo Pao Subdistrict, Gowa Regency. Using a descriptive qualitative approach grounded in Islamic community development, this research investigates the dynamics of strategic implementation through observation, in-depth interviews, and documentation. Key informants include organizational leaders, village officials, and local residents. Data analysis followed the steps of data reduction, presentation, and conclusion drawing. The findings reveal that Bangku Pelosok employs three primary strategies: a familial-based social approach, awareness campaigns and motivational initiatives, and the provision and improvement of educational facilities. These strategies have significantly impacted social change, such as increased community involvement and awareness, shifts in mindset regarding the importance of education, and greater student participation in formal education. The study recommends sustainable policy support and cross-sector collaboration to expand the strategic impact of similar organizations in other underserved areas.